Sex steroid levels in women with hypopituitarism : A case-controlled observational study - Olivius, Catharina; Landin-Wilhelmsen; Kerstin; Ohlsson; Claes; Poutanen, Matti; Trimpou, Penelope; Olsson, Daniel S; Johannsson; Gudmundur; Tivesten; Åsa (Oxford University Press, 2025)
Context
Women with hypopituitarism remain at increased risk of morbidity and mortality. Insufficient replacement of sex steroids has been suggested as a contributing factor, but sex steroid levels in women with hypopituitarism have not been comprehensively mapped.
Objective
To quantify sex steroids in women with hypopituitarism by a high-sensitivity assay.
Methods
Using a combination of clinical and biochemical criteria, women with hypopituitarism (n = 104) who started growth hormone replacement 1995-2014 at a single center were categorized as eugonadal or having hypogonadotropic hypogonadism (HH). A population-based cohort of women (n = 288) served as controls. Eugonadal women and controls were categorized as pre-/postmenopausal and HH women as younger/older (≤ or >52 years). Dehydroepiandrosterone (DHEA), androstenedione, testosterone, dihydrotestosterone, progesterone, 17αOH-progesterone, estradiol and estrone were analyzed by a validated liquid chromatography-tandem mass spectrometry assay.
Results
Among both premenopausal/younger and postmenopausal/older women, women with HH had lower levels of sex steroid precursors (DHEA, androstenedione) and androgens (testosterone and dihydrotestosterone) than controls. Progesterone, 17αOH-progesterone, estrone and estradiol showed similar patterns. Women with HH and adrenocorticotropic hormone (ACTH) deficiency had markedly lower concentrations of all sex hormones than those without ACTH deficiency.
Conclusion
This study demonstrates for the first time a broad and severe sex steroid deficiency in both younger and older women with HH, particularly in those with combined gonadotropin and ACTH deficiency. The health impact of low sex steroid levels in women with hypopituitarism requires further study and women with combined gonadotropin and ACTH deficiency should be a prioritized group for intervention studies with sex hormone replacement.